Multielectrode vs. point-by-point mapping for ventricular tachycardia substrate ablation: a randomized study. Issue 3 (9th January 2017) - Acosta, Juan; Penela, Diego; Andreu, David; Cabrera, Mario; Carlosena, Alicia; Vassanelli, Francesca; Alarcón, Francisco; Soto-Iglesias, David; Korshunov, Viatcheslav; Borras, Roger; Linhart, Markus; Martínez, Mikel; et al.
Abstract: Aims: Ventricular tachycardia (VT) substrate ablation is based on detailed electroanatomical maps (EAM). This study analyses whether high-density multielectrode mapping (MEM) is superior to conventional point-by-point mapping (PPM) in guiding VT substrate ablation procedures. Methods and results: This was a randomized controlled study (NCT02083016). Twenty consecutive ischemic patients undergoing VT substrate ablation were randomized to either group A [ n = 10; substrate mapping performed first by PPM (Navistar) and secondly by MEM (PentaRay) ablation guided by PPM] or group B [ n = 10; substrate mapping performed first by MEM and second by PPM ablation guided by MEM]. Ablation was performed according to the scar-dechanneling technique. Late potential (LP) pairs were defined as a Navistar-LP and a PentaRay-LP located within a three-dimensional distance of ≤ 3 mm. Data obtained from EAM, procedure time, radiofrequency time, and post-ablation VT inducibility were compared between groups. Larger bipolar scar areas were obtained with MEM (55.7±31.7 vs. 50.5±26.6 cm 2 ; P = 0.017). Substrate mapping time was similar with MEM (19.7±7.9 minutes) and PPM (25±9.2 minutes); P = 0.222. No differences were observed in the number of LPs identified within the scar by MEM vs. PPM (73±50 vs. 76±52 LPs per patient, respectively; P = 0.965). A total of 1104 LP pairs were analysed. Using PentaRay, far-field/LP ratio was significantly lower (0.58±0.4 vs. 1.64±1.1; P = 0.01) and radiofrequency time was shorter [median (interquartile range) 12 (7–20) vs. 22 (17–33) minutes; P = 0.023]. No differences were observed in VT inducibility after procedure. Conclusion: MEM with PentaRay catheter provided better discrimination of LPs due to a lower sensitivity for far-field signals. Ablation guided by MEM was associated with a shorter radiofrequency time.